Objective and subjective assessments of the psychological gender of female athletes practicing martial arts - Osipov, A. Y.; Kovalev, V. n.; Sadyrin, S. L.; Nagovitsyn, R. S.; Rubtsova, L. V.; Druzhinina, O. Y.; Zhavner, T. V.; Vapaeva, A. V. (SportMont, 2020)
Experts indicate the existence of a certain distorted assessment of gender in respect to female athletes practising martial arts. There is a lack of objective data regarding the determination of the predominant traits of the psychological gender of such female athletes. The purpose of the research is to compare objective and subjective data of the psychological gender of female athletes aged 18-26 practising boxing and kickboxing. The sample consisted of 58 female athletes practising boxing and kickboxing at elite and close-to-elite levels for at least five years. Psychological gender was determined using the Sandra L. Bem technique. Independent assessments of the psychological gender of female athletes and their personal trainers were also taken into account. Data analysis was performed using the Mann-Whitney U-test. The data show a significant (p<0.05) predominance of individuals with traits of the androgynous psychological gender of the total number of female athletes. A significant (p<0.01) difference was revealed between the data of an objective assessment and self-assessment of their psychological gender by female athletes. Some athletes with a masculine psychological gender endow themselves with excessive traits of androgyny. It was found that many trainers unreasonably endow their female athletes with excessive features of the masculine psychological gender.